Hybrid differential equations with maxima via Picard operators theory: Dedicated to Professor Ioan A. Rus on the occasion of his 80th anniversary - OTROCOL, Diana (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The aim of this paper is to discuss some basic problems (existence and uniqueness, data dependence) of the Cauchy problem for a hybrid differential equation with maxima using weakly Picard operators technique. Mathematics Subject Classification (2010): 47H10, 34K05.